A PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. HASNUR RIUNG SINERGI (HRS) SITE AGM: PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. HASNUR RIUNG SINERGI (HRS) SITE AGM - Norhadijah; Sulastini; Herawati, Ana Sofia (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of: (1) work ability on employee performance, (2) work motivation on employee performance, and (3) work ability and work motivation on employee performance. The design of this research is quantitative descriptive research, where the population of this research is all employees of the company PT Hasnur Riung Sinergi (HRS) Site Agm HRGS division which has 35 people and the number of samples is 35 respondents with the saturated sample method. The results showed (1) work ability has a positive and significant effect on the performance of employees of PT Hasnur Riung Sinergi (HRS) Site Agm, (2) work motivation has a positive and significant effect on the performance of employees of PT Hasnur Riung Sinergi (HRS) Site Agm and (3) work ability and work motivation have a significant effect simultaneously on the performance of employees of PT Hasnur Riung Sinergi (HRS) Site Agm. Keywords: Work Ability, Work Motivation, Employee Performance.